Factors Influencing Nurse Compliance in Implementing Pressure Ulcer Care at Martha Friska Multatuli General Hospital, Medan - Dameria Br Ginting; Herianto Bangun (International Journal of Health and Pharmaceutical (IJHP), 2026)
Compliance is the extent to which a nurse's behavior is in accordance with the provisions that have been given by the nurse leadership or the hospital. The level of compliance of nurses is not only measured by their knowledge and attitude towards the procedure, but is based on the assessment and supervision of the procedure actions. The purpose of this study is to determine the relationship of knowledge and attitudes nurses' compliance in the implementation of decubitus wound care at Martha Friska Multatuli Hospital in Medan in 2024. This study uses a correlation descriptive design with a cross sectional approach. The population in this study were all nurses at Martha Friska Multatuli Hospital Medan with a sample of 53 people. Sampling uses purposive sampling. The research data was obtained by the primary data collection method using questionnaires and secondary data from hospitals. The statistical test used is chi square (α = 0.05). The results of the research at the level of knowledge were obtained that most of the respondents had a good level of knowledge as much as 37 (69.8%), a sufficient level of knowledge of 7 (13.2%). Based on the chi square statistical test, p-value = 0.001 < α (0.05), it was found that there was a significant relationship between knowledge and nurse compliance in carrying out decubitus wound care. In the attitude of nurses, positive attitudes were obtained as many as 38 (71.7%), negative attitudes as many as 2 (3.8%) Based on the statistical test of chi square obtained p-value = 0.000 < α (0.05), it was found that there was a significant relationship between attitude and nurse compliance in carrying out decubitus wound care. The conclusion of this study is that there is a relationship between knowledge and attitudes towards nurses' compliance with the implementation of decubitus wound care at Martha Friska Mulatuli Hospital Medan in 2024. It is hoped that the hospital will provide special training on wound care to improve nursing knowledge and attitudes.